Selective deoxygenation of nitrate to nitrosyl using trivalent chromium and the Mashima reagent: reductive silylation. Issue 2 (22nd October 2018) - Seo, Junghee; Cabelof, Alyssa C.; Chen, Chun-Hsing; Caulton, Kenneth G.
Abstract : 1, 4-Bis(trimethylsilyl)-1, 4-diaza-2, 5-cyclohexadiene is an effective silyl transfer reagent towards the oxygen of nitrate coordinated to Cr(iii ) in a pincer complex. Abstract : 1, 4-Bis(trimethylsilyl)-1, 4-diaza-2, 5-cyclohexadiene is an effective silyl transfer reagent towards the oxygen of nitrate coordinated to Cr(iii ) in a pincer complex. Two nitrate oxygens are removed to give the 17 valence electron octahedral complex (H2 L)Cr(NO3 )2 (NO). This is shown by a variety of spectroscopic methods, together with DFT, to be a Cr(i ) complex with a linear CrNO unit. This work also identifies future applications of this reductive silylation process.